Self-Managed Transitional Housing and Protected Work Facilitates a New Life for People who Are Homeless: A South African Case Study - Skinner, Donald; Busakwe, Leletu; Laitinen, Jesse (International Journal on Homelessness, 2026)
Provision of housing is well established as an important first step in assisting people who are homeless, preferably with additional service support and protected work. Cost and the high population of people experiencing homelessness complicates this level of resource provision in low- and middle-income countries including South Africa. ‘Streetscapes’ established a pilot housing programme at the beginning of the coronavirus disease 2019 (COVID-19) lockdown for people experiencing homelessness. Residents also engaged in the income support programme and received supplementary services. The residents set the rules for the house, made key decisions and shared duties in the house. A partial harm reduction approach was applied, in which residents could not use substances inside the house. Evaluation tools included nine in-depth interviews with residents and staff, organizational documentation and a monthly satisfaction survey. The first six months were characterised by conflict resulting from the COVID-19 lockdowns, but once these restrictions were lifted some residents left and the remainder established order in the house. The changes in the house allowed for the development of personal responsibility and of caring responses for each other. This greater control provided a context for the residents to develop themselves, come to terms with negative habits and to collect resources for their lives off the streets. Using people who had previously experienced homelessness as supervisors facilitated care and development.